Hybrid Ultrasound and Advanced Oxidation Process Regeneration of Spent FCC Catalysts: Optimization and Their Catalytic Performance - Anggoro, Didi Dwi; Buchori , Luqman; Rinaldi, Nino; Silviana , Silviana; Le Monde, Brilliant Umara; Putra, Muhammad Fadila; Zainol, Muzakkir Mohamad (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
This study investigated the regeneration of spent fluid catalytic cracking (FCC) catalysts, which become inactive due to the accumulation of poisons at active sites. The objective of the study was to enhance acidity by regenerating spent FCC catalysts through ultrasonic and oxidation processes (UAOPs) and evaluate their effectiveness in synthesizing glycerol monostearate (GMS). The results demonstrate that spent FCC catalysts regenerated with UAOPs can significantly increase catalyst acidity, which plays a crucial role in GMS synthesis. The optimal conditions identified were temperature X1 (60 °C), regeneration time X2 (50 minutes), and flow rate X3 (9 L/h). This optimization was conducted using the Statistica 10 software, resulting in an optimal acidity value of 0.08460 mmol/gram. The GMS yield achieved was 25.33%, which was slightly higher than the yield reported in previous studies utilizing ZSM-5 and dealuminated Y catalysts for the synthesis of glycerol monostearate. Overall, this study suggests that spent FCC catalysts have potential applications in GMS synthesis